2006
DOI: 10.1272/jnms.73.75
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting Diode Phototherapy at 630.+-.3 nm Increases Local Levels of Skin-homing T-cells in Human Subjects

Abstract: Background and aims: Red light phototherapy with laser sources has been used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…Takezaki et al [21] reported that 630 VIS LED irradiation on a human leg surface resulted in the migration of T cells to the skin and the prevailing cytokine of cultured skin-homing T cells was shown to be IL-4 using transmission electron microscopy and PCR. Though the wavelength was not exactly the same as ours in this study, both wavelengths belong to near-infrared VIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takezaki et al [21] reported that 630 VIS LED irradiation on a human leg surface resulted in the migration of T cells to the skin and the prevailing cytokine of cultured skin-homing T cells was shown to be IL-4 using transmission electron microscopy and PCR. Though the wavelength was not exactly the same as ours in this study, both wavelengths belong to near-infrared VIS.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to light of immune-competent cells leads to changes in their functional condition and, consequently, to the stimulation of the immune system, manifesting itself in the increased defense capacity of an organism [17]. VIS and infrared light regulate human humoral immunity [18], manage allergic rhinitis [19], increase antitumor immunity [20] and skin-homing T cells [21], and stimulate DNA synthesis in human peripheral blood lymphocytes [22]. …”
Section: Introductionmentioning
confidence: 99%
“…Red light at 633 nm has been associated with treating the stress-related and hormonal factors of acne, in addition to its already proven effect on inflammation. 5,6 LED energy at 633 nm in humans in vivo has also been proved to recruit large numbers of Th1 and Th2 skin-homing T-cells into the irradiated skin, 13 which might help to replace the rogue Tcell population and break the vicious circle in psoriatic skin. The same combination LED therapy in a 4-week alternating regimen of 830 nm followed 24 to 72 h later by 633 nm has been convincingly and objectively shown to produce strong collagen and elastin synthesis in a large-population controlled study of skin rejuvenation.…”
Section: Ablonmentioning
confidence: 99%
“…Estudos têm demonstrado que a radiação tecidual com fontes de luz com baixa intensidade, como o diodo emissor de luz (LED) de baixa intensidade, na faixa do vermelho ao infravermelho próximo, pode ser uma estratégia efetiva para modular a dor e favorecer o processo de cicatrização tecidual (Lagan et al 2000, Lucas et al 2003, Takezaki et al 2006. Os benefícios do LED e do laser de baixa intensidade têm sido observados em condições tais como osteoartrite, radiculopatias, tendinites e, principalmente, no tratamento de feridas cutâneas em animais (Kana et al 1981, Soares et al 1989, Matera et al 2003) e em humanos (Corrêa et al 2003, Siqueira et al 2004.…”
Section: Introductionunclassified